ANALISIS KELAYAKAN DAN KONTRIBUSI PENDAPATAN USAHATANI TERPADU RUMAH TANGGA PETANI PADA LAHAN KERING - Rusli Burhansyah; Azri Azri (Agro Ekonomi, 2010)
Bengkayang district is a district in the province of West Kalimantan have enough upland for agriculture. The village of Sinar Tebudak is dry land potential for the development of food crops, vegetables, crops and livestock. To find out the feasibility of each farm and contribution to the household income required of a research. This study aims to determine the feasibility of the business of commodities grown village Sinar Tebudak and know the sources of income and multiformity contributing to the household income of farmers village Sinar Tebudak. Sinar Research conducted the survey with the method / interviews and PRA. Sampling in take with strata ownership of land. To determine the extentto which each strata in the population represented in the sample used proposional, so the methods used method stratified proportional random sampling. The number of respondents as much as 40 farmers. Collecting data is done by direct interviews with the questionnaire. Results of research show that all the farming system is feasible grown with the value RIC> 1. The agricultural sector still has a major contribution in the household contribute income farmers. Income per capita village Sinar Tebudak already above U.S. $ 1000. Non agricultural sector and other sectors in rural areas is expected to grow well. Development of agro-industries in rural areas will create the market, and production facilities for primary agricultural products.